Party “Istrian Democratic Assembly” and Regional Issues in Contemporary Croatia - Al. Al. Pivovarenko (Сравнительная политика, 2024)
The purpose of the article is to characterize the political platform of the Istrian Democratic Assembly (IDS), Croatia, as a political power advocating for the idea of regional autonomy for the Istrian peninsula. Based on the analysis of an extensive database of empirical materials, this article explores the main points of the political ideology of IDS, the nature of its relations with the political center of Croatia, as well as its international cooperation with European organizations and neighboring states. The comprehensive study of this political party and its history between 1991 and 2022 provides a detailed insight into the so-called Istrian regional movement. It is less evident when comparing to similar movements in Southern or Western Europe but still distinct due to its development within both the ethnopolitical context of the Balkan peninsula and the European regionalist movements. Thus the detailed study of this issue gives a detailed picture of internal political trends of the Balkans and the countries in the periphery of the European Union.